Endoscopic Removal of a Nitinol Mesh Stent from the Ureteropelvic Junction after 15 Years. (1st December 2015) - Smrkolj, Tomaž; Šalinović, Domagoj
Abstract : We report a rare case of a patient with a large stone encrusted on a nitinol mesh stent in the ureteropelvic junction. The stent was inserted in the year 2000 after failure of two pyeloplasty procedures performed due to symptomatic ureteropelvic junction stenosis. By combining minimally invasive urinary stone therapies—extracorporeal shock wave lithotripsy, semirigid ureterorenoscopy with laser lithotripsy, and percutaneous nephrolithotomy—it was possible to completely remove the encrusted stone and nitinol mesh stent that was implanted for 15 years, rendering the patient symptom and obstruction free.